COMPARING LECTURE AND INTERACTIVE DISCUSSION METHODS TO ENHANCE HEPATITIS B KNOWLEDGE IN PREGNANT WOMEN AND COUPLES IN GONDANGLEGI - Supriono, Supriono; Wibowo, Bogi Pratomo; Mustika, Syifa; Fachrureza, Mochamad; Imroatussholihah, Al; Prayitno, Tia Rahmi; Amalia, Dinda; Nugroho, Rama Tiar (Caring: Jurnal Pengabdian Masyarakat, 2025)
Hepatitis B is a global health issue that has a significant impact on society, especially in terms of the risk of transmission from mother to child during childbirth. Health education is an important effort to prevent the spread of infection, particularly among pregnant women. This community service activity aims to increase knowledge about hepatitis B among pregnant women and reproductive-age couples in Gondanglegi, Malang, through two educational methods: lectures and interactive discussions. The lecture was conducted using a conventional approach, where information about hepatitis B was delivered directly to participants with the aid of visual PowerPoint materials to clarify the content. Meanwhile, the interactive discussion involved several speakers discussing the topic of hepatitis B, allowing participants to engage in discussions, share experiences, and ask questions to the speakers. Both methods were effective in increasing participants' knowledge, with the lecture method providing a more significant improvement. This activity is expected to strengthen public understanding of hepatitis B, while also supporting efforts to prevent the transmission from pregnant women to their babies.